Petrochronology of Alkaline Intrusive Magmatism in the Central High‐Atlas (Morocco) and Relationships With Jurassic Salt Diapirism - Youssef Ahechach; Muhammad Ouabid; Françoise Roger; Fleurice Parat; Otmane Raji; Jean‐Marie Dautria; Valérie Bosse; Cheikh Elwali Malainine; Hicham El Messbahi; Hamza Skikra; Jean‐Louis Bodinier (Geochemistry, Geophysics, Geosystems)
Abstract A striking feature of the Imilchil alkaline province, in the Moroccan Central High Atlas, is the close association of magmatic intrusions with Triassic sediments exhumed by diapirism. This study reports field, petrographic, geochemical and Sr‐Nd isotopic data, as well as new U‐Pb zircon ages, which allow us to constrain the timing of the intrusions and to discuss their relationship to diapiric structures and the magmatic and hydrothermal processes. Our results indicate a restricted range of Late Jurassic ages (ca. 163 ± 1—ca. 149 ± 2 Ma) for the paroxysm of magmatic activity and confirm the diachronicity between diapirism and magmatism, albeit with a short interval of only a few My between the end of diapirism and the magmatic paroxysm. Deep‐seated faults associated with transtensional tectonics, accommodating the increasing spreading rate of the Central Atlantic during the Jurassic, played a key role in the close association of magmatic intrusions with diapirs. The faults first triggered active diapirism in the Early‐ Jurassic and then guided OIB‐type partial melts formed by local decompression melting of the mantle. At shallower depths, the diapiric structures acted as corridors for magma migration, probably using evaporites as preferential pathways. Magmas underwent fractional crystallization and interacted with evaporites to produce pervasive Na‐rich hydrothermal fluids.